Efektivitas Kegiatan Kuliah Tujuh Menit (Kultum) Dalam Membentuk Kepercayaan Diri Siswa Kelas V Di SDIT Assalam Garut Kota - Izzan, Ahmad; Oktaviani , Nopi (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Self-confidence is a crucial element for students to develop their potential effectively. However, issues surrounding students' self-confidence often demand significant attention. Indicators of low self-confidence among students include a lack of self-belief, optimism, objectivity, responsibility, and rational as well as realistic thinking. Consequently, these students struggle to harness their full potential. One viable approach to addressing this issue is through the implementation of the "seven-minute lecture" (kultum) activity. This study aims to describe the effectiveness of kultum activities in fostering self-confidence among fifth-grade students at SDIT Assalam Garut Kota. The research employs a descriptive quantitative approach. Data collection methods include observations, document analysis, and questionnaires. The research sample consists of 28 fifth-grade students from SDIT Assalam Garut Kota. Data were processed using statistical analysis methods. The results of the study indicate that the effectiveness of the kultum activity is rated with an average score of 3.57, falling within the 3.01-4.00 interval, which is categorized as "Good". This demonstrates that the kultum activities were executed effectively. Furthermore, the development of students' self-confidence was rated with an average score of 4.32, within the 4.01-5.00 interval, categorized as "Very Good". This indicates a significant increase in students' self-confidence following the effective implementation of kultum activities. Statistical tests reveal a significant correlation of 34.3% between participation in kultum activities and the enhancement of students' self-confidence, with other unexamined variables contributing 65.7% to the development of self-confidence.  Keywords: Effectiveness, Kultum Activities, Self-Confidence